Twitter, social services and covid-19. Analysis of the communicative interactions of the communicative interactions of the messages emitted by political parties, social political parties, social entities, and citizens - Chaves-Montero, Alfonso (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2023)
The state of alarm caused by Covid-19 has mobilised the digital social participation of the population in social networks. Likewise, the relevance acquired by Social Services in the socio-health crisis has generated an unprecedented social debate on Twitter about the reality of these services. In the article, tweets about Social Services and Covid-19 published during the pandemic were analysed using Atlas.Ti software. The results show the precariousness of Social Services and the need for a change in the management and financing model of these services in order to guarantee social benefits.